2016
DOI: 10.1016/j.beproc.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Vocal individuality and species divergence in the contact calls of banded penguins

Abstract: Penguins produce contact calls to maintain social relationships and group cohesion. Such vocalisations have recently been demonstrated to encode individual identity information in the African penguin. Using a source-filter theory approach, we investigated whether acoustic cues of individuality can also be found in other Spheniscus penguins and the acoustic features of contact calls have diverged within this genus. We recorded vocalisations from two ex-situ colonies of Humboldt penguin and Magellanic penguin (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…Moreover, recently, in the African penguin it has been demonstrated that both the source- and filter- related components can encode individual identity information [ 10 ]. Overall, our findings support the hypothesis that in nesting penguins, the acoustic cues to identity are the fundamental frequency and the energy distribution across the spectrum [ 33 , 55 ] and that studying the anatomical constraints that influence the vocal output with a source-filter theory approach can lead to a better understanding of the individual identity information encoded in their vocalisations [ 10 , 31 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, recently, in the African penguin it has been demonstrated that both the source- and filter- related components can encode individual identity information [ 10 ]. Overall, our findings support the hypothesis that in nesting penguins, the acoustic cues to identity are the fundamental frequency and the energy distribution across the spectrum [ 33 , 55 ] and that studying the anatomical constraints that influence the vocal output with a source-filter theory approach can lead to a better understanding of the individual identity information encoded in their vocalisations [ 10 , 31 ].…”
Section: Discussionsupporting
confidence: 80%
“…These measurements included temporal measures, such as call duration which is related to lung capacity [ 45 ], source-related vocal features ( f 0 ) which are related to the vibrating mass in the syrinx [ 46 ], and filter- related features (formants), related to the supra-syringeal vocal tract [ 18 ]. Specifically, following the visual inspection of the spectrograms and previous acoustic response of vocal tract models for Spheniscus penguins [ 10 , 31 ], we extracted the contour of the first four formants ( F 1 – F 4 ) of each vocalisation. We used a Linear Predictive Coding and we set to 5 the maximum number of formants to be tracked by the Praat software below 4000Hz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vocal characteristics in penguins are relatively understudied compared to other bird taxa, but studies have shown gradual interspecies differentiation over time (Thumser et al 1996, Favaro et al 2016 Seddon andvan Heezik 1993, Favaro et al 2016), Magellanic Penguins (S. magellanicus; Clark et al 2006), and Macaroni Penguins (E. chrysolophus; Searby et al 2004). These studies all indicate that while there may be differences in complexity between species, vocalizations play an important role in behavior across all penguins.…”
Section: Introductionmentioning
confidence: 94%